MANAGEMENT OF PESTICIDE CONTAMINATION IN THE ENVIRONMENT AND AGRICULTURAL PRODUCTS: A LITERATURE REVIEW - Globila Nurika; Reny Indrayani; Ana Islamiyah Syamila; Dhuha Itsnanisa Adi (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: The use of pesticides not only has benefits for product growth but also causes problems with the entry of pesticide residues in the food chain to pollution to the environment. This study aims to formulate ways to reduce pesticide contamination in the environment and agricultural products. Discussion: This literature review was conducted using the PRISMA method using 35 articles 14 of which were published in the ScienceDirect database, 12 in the Proquest database, and 9 in the Pubmed database. Environmental pollution due to pesticides is caused by the behavior of spraying pesticides and disposing of used pesticides by farmers. Ways to reduce it are by measuring how much pesticide is needed, training to increase knowledge about agricultural practices in preparing the required dose, and regularly monitoring environmental quality. Pesticide residues can increase due to the application of pesticides at harvest, and they can be reduced by washing, peeling, and cooking processes. In addition, another proven effective way to reduce pesticide residues is using an electrolyzed water treatment, sonolytic ozonation, and ozonated water. Conclusion: The use of unsafe pesticides will harm the environment and endanger health through the food chain. Training for farmers to use pesticides properly is considered effective in reducing pesticide pollution in the environment. In addition, the reduction of pesticides in agricultural products can be done by washing, peeling, cooking (boil, boil and fry), electrolyzed water treatment, sonolytic ozonation, and ozonated water.